2015
DOI: 10.1164/rccm.201411-1995oc
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Infection by Mucoid Pseudomonas aeruginosa Associated with Dysregulation in T-Cell Immunity to Outer Membrane Porin F

Abstract: Rationale: Pseudomonas aeruginosa (PA) is an environmental pathogen that commonly infects individuals with cystic fibrosis (CF) and non-CF bronchiectasis, impacting morbidity and mortality. To understand the pathobiology of interactions between the bacterium and host adaptive immunity and to inform rational vaccine design, it is important to understand the adaptive immune correlates of disease.Objectives: To characterize T-cell immunity to the PA antigen outer membrane porin F (OprF) by analyzing immunodominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…Although the Bp immunome is clearly large and complex, the definition of highly immunodominant, common, peptide-HLA complexes offers the potential for developments in future immune monitoring of immune status 12 14 , 22 , 23 . A new tool developed from analysis of Bp pMHC and Pseudomonas aerguniosa 24 pMHC complexes in responder datasets is BIITE, a means of elucidating likely pMHC combinations out of bulk PBMC responses in HLA-heterozygous individuals who will be expressing multiple HLA class II heterodimers to present peptide 23 . AhpC, and specifically, the p6 epitope from this antigen, stand out as a part of the Bp immunome that is highly visible to the T cell repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Bp immunome is clearly large and complex, the definition of highly immunodominant, common, peptide-HLA complexes offers the potential for developments in future immune monitoring of immune status 12 14 , 22 , 23 . A new tool developed from analysis of Bp pMHC and Pseudomonas aerguniosa 24 pMHC complexes in responder datasets is BIITE, a means of elucidating likely pMHC combinations out of bulk PBMC responses in HLA-heterozygous individuals who will be expressing multiple HLA class II heterodimers to present peptide 23 . AhpC, and specifically, the p6 epitope from this antigen, stand out as a part of the Bp immunome that is highly visible to the T cell repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterium Pseudomonas Aeruginosa (PA) is an environmental organism that can cause infection in damaged lung or the immune compromised host. PBMCs from a small cohort (N = 58) of patients with a chronic lung disease associated with recurrent lung infection and progressive lung damage, called bronchiectasis, were used to test 34 overlapping 20-mers of the OprF protein using IFNγ ELISpot assays [ 15 ]. We used a cut-off of 2SD above the mean of medium only control to decide whether a particular ELISpot result for an individual was positive or negative.…”
Section: Methodsmentioning
confidence: 99%
“…Analogously to the Burkholderia dataset, we had access to a immunogenicity data derived from transgenic mouse models and binding data from peptide-binding assays [ 15 ]. Transgenic mouse models were available for DRB1*01 , DRB1*04 and DRB1*15 ; binding data was available for 7 HLA-DRB1 alleles.…”
Section: Methodsmentioning
confidence: 99%
“…When the infection was eradicated after treatment with colistin, VEGF‐A levels further increased supporting a role of VEGF‐A in the healing process of the lung. Although a chronic P. aeruginosa lung infection is associated with IFNγ responses from T‐lymphocytes, the animal data in this study showed unchanged concentrations in lung tissue over time, indicating innate immunity as the site of IFNγ production.…”
Section: Discussionmentioning
confidence: 55%